ANALISA PUTUSAN HAKIM TERHADAP PERUSAHAAN RETAIL YANG MELAKUKAN PENGUMPULAN DONASI BERDASARKAN STATUS PERUSAHAAN: Studi Kasus Putusan No. 16/Pdt.G/2017/PN.Tng) - Shania Revita Fajriyani (2021)
Retail companies in Indonesia contribute and also absorb a large workforce, one of which is PT. Sumber Alfaria Trijaya Tbk., apart from being a provider of various basic needs and consumer services, the company also mobilizes financial assistance as a donation to help people in need. As a result of one of these donations, PT. Sumber Alfaria Trijaya Tbk. must undergo legal proceedings at the Tangerang District Court with Decision Number: 16 / Pdt.G / 2017 / PN.Tng for refusal to inform the donation so that there is no transparency to the public in accordance with Law Number 14 of 2008 concerning Openness of Public Information. The content of the verdict contains a clear claim by PT. Sumber Alfaria Trijaya Tbk. refused to be declared a public body because the retail company was clearly a private legal entity that was engaged in business. However, in this case, the judge only considers the exception as an error in person so that it will not give legal considerations related to arguments and evidence relating to the subject matter of the case. The method used is normative juridical. Approach the problem by using the statutory approach and the case approach, the main source comes from the literature and uses secondary data sources that are analyzed qualitatively. Based on the results of the decision of the Tangerang District Court on the case of PT. Sumber Alfaria Trijaya Tbk, based on the things that contain the provisions of the reasons for the retail company to be transparent and / or not transparent to the public regarding the implementation of contributions made as a source of funding from the public.